Implementation of Quizizz Online Evaluation Tools With STEM Approach to Measure Analytical Skills of the Junior High School Students - Seyla Anggraeni*; Muhamad Taufiq (Program Studi Magister Pendidikan IPA Program Pascasarjana Universitas Syiah Kuala, 2021)
The evaluation process at SMP Kesatrian 1 Semarang based on the results of observations cannot be used to measure analytical skills of the students. Based on observation, the average analytical ability of students still at low criteria. The purpose of this research is to measure analytical skillsof the students using Quizizz application with STEM approach. This is a pre-experimental research with one shoot case study design. Population of this research is all students of grade 8 Kesatrian 1Junior high school of Semarang Central Javain the 2019/2020 school year. The sampling technique was carried out by purposive sampling with a sample of 30 students. The instrument used in this researchare analytical skills test of students using Quizizz application with STEM approach and questionnaire of students response about Quizizz as evaluation tool. Students are attending the lesson according to the lesson plan and are evaluated at the end of the lesson using the online Quizizz application as evaluation tool with a STEM approach. The result of test is quantitative data that analyzed descriptively. The results indicated the profile of analytical skills of the studentsare of 6.67%in the high criteria, 73.33% inmoderate criteria and 20% in low criteria. It can be concluded that the average analytical skills of the students at Kesatrian 1 junior high school of Semarang is in moderate criteria.Finally, the research provides teacher recommendations to applying Quizizz application with STEM approach to measure analytical skills of the students in early learning environments